New Music Recommendation Algorithm Facilitates Audio Branding - Bertram Barth; Silke Borgstedt; James Edwards (Marketing Review St.Gallen, 2019)
While marketing continues to work primarily in a visual domain, holistic brand experiences and multisensory marketing techniques are becoming ever more important. Audio branding is one such technique. The European Commissionfunded research and innovation project ABC_DJ has developed an algorithmic music recommender system specifically for use in audio branding. The system's core function is to assist marketers in determining musical brand fit, i.e. whether listeners will evaluate a given piece of music as fitting the perceived attributes of a given brand, and target group preference, i.e. whether listeners belonging to a particular target group will like a given piece of music. This article describes the ABC_DJ project's aims, outputs, commercial applications, and status as an asset for European SMEs facing the ongoing evolution of the point of sale into a point of experience.
Keywords: 650